aMixer Mini-Data Acquisition System: An Optimization Approach to Observe of the HCl-Sodium Thiosulfate Reaction - Nabira Salwa; Ijang Rohman; Miarti Khikmatun Nais; Achmad Mudzakir; Gun Gun Gumilar (Jurnal Penelitian Pendidikan IPA, 2026)
In determining the reaction rate between hydrochloric acid (HCl) and sodium thiosulfate (Na₂S₂O₃), conventional experiments commonly rely on visual observation of sulfur turbidity, making endpoint determination highly dependent on lighting conditions and observer judgment. These limitations reduce measurement accuracy, repeatability, and objectivity, highlighting the need for an alternative Data Acquisition System (DAS) capable of providing continuous quantitative measurements. This study focuses on the development and optimization of a Data Acquisition System (DAS) utilizing transducers and photodetectors through the Research Science Design (RSD) approach as an alternative method for reaction kinetics analysis. The experimental setup consisted of a borosilicate reactor enclosed in a black acrylic chamber to minimize ambient light interference, equipped with 3 W high-power LEDs (green, blue, and white) as light sources and a Mini Mixer interface integrated with MGA software for continuous data acquisition. Each LED configuration was evaluated through three experimental repetitions, and the recorded signals were analyzed using Relative Standard Deviation (RSD) to assess measurement stability and determine the optimum light source. Based on the evaluation results, the DAS was capable of (1) continuously recording sulfur colloid formation in real time, (2) demonstrating the highest measurement stability under green light with an RSD of 1.18%, and (3) eliminating observer-dependent visual bias. The proposed system provides a simple, coding-free, objective, and affordable solution for improving the quality and efficiency of reaction kinetics measurements in chemistry education.